Systematic study of intermediate-scale structures of equatorial plasma irregularities in the ionosphere based on CHAMP observations - Lühr, Hermann; Xiong, Chao; Park, Jaeheung; Rauberg, Jan (Frontiers in Physics, 2014)
Equatorial spread-F ionospheric plasma irregularities on the night-side, commonly called equatorial plasma bubbles (EPB), include electron density variations over a wide range of spatial scales. Here we focus on intermediate-scale structures ranging from 100 m to 10 km, which play an important role in the evolution of EPBs. High-resolution CHAMP magnetic field measurements sampled along north-south track at 50 Hz are interpreted in terms of diamagnetic effect for illustrating the details of electron density variations. We provide the first comprehensive study on intermediate-scale density structures associated with EPBs, covering a whole solar cycle from 2000 to 2010. The large number of detected events, almost 9000, allows us to draw a detailed picture of the plasma fine structure. The occurrence of intermediate-scale events is strongly favoured by high solar flux. During times of F10.7 < 100 sfu practically no events were observed. The longitudinal distribution of our events with respect to season or local time agrees well with that of the EPBs, qualifying the fine structure as a common feature, but the occurrence rates are smaller by a factor of 4 during the period 2000-2005. Largest amplitude electron density variations appear at the poleward boundaries of plasma bubbles. Above the dip-equator recorded amplitudes are small and fall commonly below our resolution. Events can generally be found at local times between 19 and 24 LT, with a peak lasting from 20 to 22 LT. The signal spectrum can be approximated by a power law. Over the frequency range 1 – 25 Hz we observe spectral indices between -1.4 and -2.6 with peak occurrence rates around -1.9. There is a weak dependence observed of the spectral index on local time. Towards later hours the spectrum becomes shallower. Similarly for the latitude dependence, there is a preference of shallower spectra for latitudes poleward of the ionisation anomaly crest. Our data suggest that the generation of small plasma structure